2019
DOI: 10.1101/799163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Runx1 promotes scar deposition and inhibits myocardial proliferation and survival during zebrafish heart regeneration

Abstract: Runx1 is a transcription factor that plays a key role in determining the proliferative and differential state of multiple cell-types, during both development and adulthood. Here, we report how runx1 is specifically upregulated at the injury site during zebrafish heart regeneration, but unexpectedly, absence of runx1 results in enhanced regeneration. Using single cell sequencing, we found that the wild-type injury site consists of Runx1-positive endo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 62 publications
4
11
0
Order By: Relevance
“… 51–53 More recently, RUNX1 has been shown to be involved in zebrafish heart regeneration following cardiac injury. 54 Cryo-injury resulted in increased RUNX1 expression within various cell types of the myocardium including cardiomyocytes, myofibroblasts, endocardial/endothelial, epicardial, and thrombocytes, where it inhibits heart repair.…”
Section: Runx1 Expression In Cardiac Injurymentioning
confidence: 99%
See 2 more Smart Citations
“… 51–53 More recently, RUNX1 has been shown to be involved in zebrafish heart regeneration following cardiac injury. 54 Cryo-injury resulted in increased RUNX1 expression within various cell types of the myocardium including cardiomyocytes, myofibroblasts, endocardial/endothelial, epicardial, and thrombocytes, where it inhibits heart repair.…”
Section: Runx1 Expression In Cardiac Injurymentioning
confidence: 99%
“…The link between RUNX1 and adverse cardiac remodelling has now been corroborated by others in mice 81 and also in cryo-injured zebrafish hearts, where Runx1 knockout prevented adverse cardiac remodelling by promoting faster scar degradation. 54 The cellular composition of the scar was differentially regulated so that smooth muscle and collagen gene expression was significantly reduced, subsequently reducing the amount of collagen, and fibrin deposition. Myofibroblast formation was also reduced whilst fibrinolysis increased, thus allowing invasion of proliferative cardiomyocytes and hence enhancing muscle regeneration.…”
Section: Runx1 and Adverse Cardiac Remodellingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that the transcription factor Runx1 is a key regulator of both scar deposition and degradation, as well as proliferation of the myocardium (Koth et al 2020 ). Not only was Runx1 seen to be specifically upregulated in endocardial cells and thrombocytes in the injury region, which in turn induced expression of smooth muscle and collagen genes during zebrafish heart regeneration, but targeted mutation and the subsequent absence of runx1 resulted in an increase in survival and proliferation of the myocardium and overall heart regeneration and decreased fibrosis resulting from a reduction in myofibroblast formation and upregulation of the fibrin degeneration pathway (Koth et al 2020 ).…”
Section: Extracellular Vesicles Cilia and Signalling Networkmentioning
confidence: 99%
“…It has recently been shown that the transcription factor Runx1 is a key regulator of both scar deposition and degradation, as well as proliferation of the myocardium (Koth et al 2020 ). Not only was Runx1 seen to be specifically upregulated in endocardial cells and thrombocytes in the injury region, which in turn induced expression of smooth muscle and collagen genes during zebrafish heart regeneration, but targeted mutation and the subsequent absence of runx1 resulted in an increase in survival and proliferation of the myocardium and overall heart regeneration and decreased fibrosis resulting from a reduction in myofibroblast formation and upregulation of the fibrin degeneration pathway (Koth et al 2020 ). This discovery is particularly interesting given that Runx1 is upregulated in CMs post-injury in a number of species, both regenerative and not, and presents a potential therapeutic target that could be manipulated to induce endogenous human heart regeneration (Gattenlöhner et al 2003 ; Kubin et al 2011 ; Eulalio et al 2012 ; Górnikiewicz et al 2016 ; Goldman et al 2017 ; Koth et al 2020 ).…”
Section: Extracellular Vesicles Cilia and Signalling Networkmentioning
confidence: 99%